Text Type Classification in the Japanese Language - Andrej BEKEŠ (Acta Linguistica Asiatica, 2012)
This paper deals with some recent approaches to Japanese text classification within the framework of Halliday’s systemic functional linguistics. Text types differ according to the properties of their respective field, tenor and mode. Classification approaches usually center on field properties as reflected in content words and their distribution in texts. On the other hand, approaches introduced in the present paper are based on evidential-modal meanings, expressed by evidential adverbs and sentence-final auxiliary evidential-modal expressions.